2018
DOI: 10.1007/s00125-018-4769-x
|View full text |Cite
|
Sign up to set email alerts
|

Skin autofluorescence predicts incident type 2 diabetes, cardiovascular disease and mortality in the general population

Abstract: Aims/hypothesisEarlier studies have shown that skin autofluorescence measured with an AGE reader estimates the accumulation of AGEs in the skin, which increases with ageing and is associated with the metabolic syndrome and type 2 diabetes. In the present study, we examined whether the measurement of skin autofluorescence can predict 4 year risk of incident type 2 diabetes, cardiovascular disease (CVD) and mortality in the general population.MethodsFor this prospective analysis, we included 72,880 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 49 publications
4
69
0
Order By: Relevance
“…With the benefit of a longer observation period resulting in a greater number of outcome events, we have confirmed that higher baseline SAF and increase in SAF over 1 year are independent predictors of CVEs and ACM in early stage CKD after adjustment for traditional risk factors and, importantly, also CRP. One study has reported that higher SAF predicted incident diabetes, CVEs, and ACM in a large cohort enrolled from the general population [20].…”
Section: Plos Medicinementioning
confidence: 99%
“…With the benefit of a longer observation period resulting in a greater number of outcome events, we have confirmed that higher baseline SAF and increase in SAF over 1 year are independent predictors of CVEs and ACM in early stage CKD after adjustment for traditional risk factors and, importantly, also CRP. One study has reported that higher SAF predicted incident diabetes, CVEs, and ACM in a large cohort enrolled from the general population [20].…”
Section: Plos Medicinementioning
confidence: 99%
“…54 In a median 4-year follow-up study of more than 70,000 participants without diabetes or CVD, SAF was shown to predict the development of type 2 diabetes, CVD, and death, independently of classical risk factors. 55 Accumulation of CML increases in the atrial appendage of patients with atrial fibrillation, which is associated with severity of fibrosis in both diabetic and non-diabetic subjects. 56,57…”
Section: Tissue Levels Of Ages and Cvdmentioning
confidence: 99%
“…Noninvasive measures of AGEs such as SAF might be useful in the pediatric setting. Recently, SAF was shown to predict future type 2 diabetes and cardiovascular disease risk irrespective of metabolic health, supporting the utility of this measure and the subclinical effects of AGEs on health. As indicated above, we did not perform a comprehensive evaluation of cardiovascular and metabolic health; however, our results involving the relationship between pentosidine and insulin resistance support future work in this area.…”
Section: Discussionmentioning
confidence: 85%